La gouvernance de l’orpaillage clandestin dans les localités ivoiriennes frontalières du Mali et du Burkina Faso - Kouamé Hyacinthe Konan (EchoGéo)
Debates on clandestine gold panning in Côte d'Ivoire have long focused on the environmental damage that this activity causes to the environments in which gold mining sites are located. Although spatial disorder remains the most striking feature of mining sites, this activity masks a solid operating logic that structures its management. Beyond this apparent disorder, clandestine gold panning is highly structured and functions on the basis of regulatory mechanisms that are based on the strategic application of norms that are constructed on the margins of formal norms. The aim of this paper is to shed light on these mechanisms that underpin the governance of illegal gold mining. The methodology is based on field surveys carried out in the localities of Kalamon, Gôgô and zanikahan located respectively in the departments of Doropo, Téhini and Tingrela on the border with Mali and Burkina Faso. The results of this study show that the mechanisms regulating clandestine gold panning are certainly unstable, but they make artisanal gold mining sites governed spaces, far removed from the idea of 'generalised anarchy' which dominates the discourse on clandestine gold panning. Also, the choice of coercive means to put an end to gold panning rather than participatory management including public authorities and local populations contributes to the creation of these 'no responsibility' zones where operators organise the exploitation of mineral resources without being accountable for its consequences